Introducing English grammar - Borjars, Kersti; Burridge, Kate (New York, NY : Routledge, 2019)
'Introducing English Grammar introduces readers to the methodology and terminology needed to analyse English sentences. The approach taken is in line with current research in grammar, a particular advantage for students who may go on to study syntax in more depth. All the examples and exercises use real language taken from newspaper articles, non-standard dialects and include excerpts from studies of patients with language difficulties. Students are encouraged to think about the terminology as a tool kit for studying language and to test what can and cannot be described using these tools. This new edition has been fully updated and features: - an expanded introduction; - new texts and exercises that include data from social media; - revised material on Grammar at work and English worldwide; - a new discussion on recent developments in the study of noun phrase and clausal structure; - more suggestions for further reading at the end of each chapter; - a brand-new companion website with extensive further reading and answers to the exercises, which can be found at www.routledge.com/cw/borjars. Written for readers with no previous experience of grammatical analysis, Introducing English Grammar is suited to anyone beginning a study of linguistics, English language or speech pathology, as well as to students with primary literary interests who need a better understanding of the structure of English'--
Introduction: the glamour of grammar -- The structure of sentences -- The words of English -- Functions within the clause -- Different sentence types -- The verb phrase -- The noun phrase -- Clauses within clauses -- Beyond the sentence -- Grammar at work -- English worldwide.
Includes bibliographical references and index.
Includes bibliographical reference : page [317] and index
Keywords: English language -- Grammar